The Impact of the Work Environment on the Performance of Nurses in the Saudi Healthcare Sector - Althobaiti, Khalid Mansour; Alkhiri, Abdullah Ali Hamzah; Alzubaidi, Badrah Ibrahim; Abdullah, Balker Muhammad; Alrashdi, Ali Hassan Mohammed; Alkhairi, Obaid Ali; Alfayz, Abrar Fawaz; Almbrook, Haya Ali; Altherwi, Amani Hassan; Aljaloud, Faris Sulaiman (Journal of Economic, Administrative and Legal Sciences, 2023)
The study examined how various aspects of the work environment impact nurses' performance in Saudi government hospitals. It focused on dimensions like training, incentives, technological empowerment, work nature, conditions, and participation in decision-making. Using a descriptive-analytical approach, the study surveyed 112 nurses from hospitals in Riyadh, Jeddah, and Al-Qunfudhah. The findings showed that work environment dimensions had a significant influence, with an R-square value of 0.898, explaining 89.8% of the variation in nurse performance. The study also validated a model for predicting nurse performance based on overall work environment scores. In light of these findings, the study recommends enhancing hospital management strategies. This includes providing modern technology and medical equipment to improve job performance within the work environment. Additionally, the study suggests boosting motivation and empowerment among nurses to increase their sustainability and efficiency. It emphasizes the importance of hospitals addressing all work environment dimensions adequately to enhance nurses' ability to deliver high-quality healthcare services. This research underscores the critical role of the work environment in shaping nurses' performance in the Saudi healthcare sector.
Keywords: Work Environment; Nurse Performance; Healthcare Sector; Kingdom of Saudi Arabia